2013
DOI: 10.19026/rjaset.5.4661
|View full text |Cite
|
Sign up to set email alerts
|

Gas Chromatography/Electron Ionization Mass Spectrometric Analysis of Oligomeric Polyethylene Glycol Mono Alkyl Ethers

Abstract: Polyethylene Glycol Monoalkyl Ethers, C x H 2x+1 (OC 2 H 4 ) n OH, (PEGMAE), are polar compounds like Polyethylene Glycols (PEG) and they undergo microbial degradation which produces toxic substances that are potentially dangerous to the environment. Therefore, the purpose of this study is to carry out proper identification and characterization of these compounds. The Electron Ionization (EI) and Chemical Ionization (CI) spectra of various PEGMAE were obtained by Gas Chromatography/Mass Spectrometry (GC/MS) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Conversely, it almost fits perfectly with a compound having a minimal formula C5H13NO2 2.2.7.). This data fits with the finding of Onigbinde et al (2013), who found that methane positive-ion mode chemical ionization of PEGs gives rise to spectra in which the peaks consist mostly of MH + , (C2H4O)nH + , (H(OC2H4)nOH)H2 + , and CH3(OC2H4)n + ions and small amount of C2H5OC2H4 + ions (Onigbinde et al, 2013).…”
Section: 22) Due To the Physicochemical Property Of The Attachedsupporting
confidence: 90%
“…Conversely, it almost fits perfectly with a compound having a minimal formula C5H13NO2 2.2.7.). This data fits with the finding of Onigbinde et al (2013), who found that methane positive-ion mode chemical ionization of PEGs gives rise to spectra in which the peaks consist mostly of MH + , (C2H4O)nH + , (H(OC2H4)nOH)H2 + , and CH3(OC2H4)n + ions and small amount of C2H5OC2H4 + ions (Onigbinde et al, 2013).…”
Section: 22) Due To the Physicochemical Property Of The Attachedsupporting
confidence: 90%
“…In addition, we have also observed the peaks corresponding to CO 2 (AMU 16, 28, and 44), which appeared only at a temperature above 160 °C. The obtained results (Table S1) were in agreement with the reported literature. , …”
Section: Resultsmentioning
confidence: 99%
“…The obtained results (Table S1) were in agreement with the reported literature. 60,61 The TGA−MS analysis was further carried out on the crosslinked P95 polymer electrolyte sample, and the result is reported in Figure 3B and Table S1, which exhibited more or less similar peaks corresponding LiBF 4 and PEGDGE. The major change for P95 from the oligomer and the salt was that the BF 3 peak was absent in the polymer sample.…”
Section: Resultsmentioning
confidence: 99%